Thermal creep and the skyrmion Hall angle in driven skyrmion crystals. (31st December 2018) - Reichhardt, C; Reichhardt, C J O
Abstract: We numerically examine thermal effects on the skyrmion Hall angle for driven skyrmions interacting with quenched disorder. We identify a creep regime in which motion occurs via intermittent jumps between pinned and flowing states. Here the skyrmion Hall angle is zero since the skyrmions have time to relax into equilibrium positions in the pinning sites, eliminating the side-jump motion induced by the Magnus force. At higher drives we find a crossover to a viscous flow regime where the skyrmion Hall angle is finite and increases with increasing drive or temperature. Our results are in agreement with recent experiments which also show a regime of finite skyrmion velocity with zero skyrmion Hall angle crossing over to a viscous flow regime with a skyrmion Hall angle that increases with drive.